2019
DOI: 10.1002/1348-9585.12033
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a smart chair and corresponding smartphone app as an objective measure of desk-based sitting

Abstract: Objectives This study evaluated the validity of a smart chair and corresponding smartphone app (chair&app) to measure sitting time and sitting interruptions against camera‐derived observation and activPAL. Methods Belgian deskbound university employees (n = 28, 17 women, mean age 30 ± 7.5 years, mean BMI 22.1 ± 2.0 kg/m 2 ) were provided with the chair&app in three conditions: a controlled condition (following a prescribed protocol), a free‐li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…With the rapid development of modern technology, noncontact measurements have been applied to seat comfort/discomfort evaluation such as radiography [ 96 ], ultrasonography [ 97 , 98 ] and MRI [ 99 , 100 , 101 ]. After installing specific apps, smart phones could be turned into portable sitting posture recorders, which could be used to study motion as traditional products once did [ 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of modern technology, noncontact measurements have been applied to seat comfort/discomfort evaluation such as radiography [ 96 ], ultrasonography [ 97 , 98 ] and MRI [ 99 , 100 , 101 ]. After installing specific apps, smart phones could be turned into portable sitting posture recorders, which could be used to study motion as traditional products once did [ 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the ability of the W@W-App+MetaWearC to detect sitting and standing postures based on thigh acceleration. Recent studies have developed and validated self-monitoring devices that also provide real-time feedback on an integrated display, including the SitFit [ 32 ] or through a mobile phone app via Bluetooth synchronization such as the VitaBit [ 33 ] and Chair&App [ 34 ]. Similar to the findings presented here, the SitFit and Chair&App devices reported that sitting time was highly accurate when compared to the activPAL3M in free-living conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation coefficient of the sensor reading with the tape measure of the distance between the sound notification sensor and the subject was 0.998 (Figure 1). 19…”
Section: Digital Sound Notification Sensormentioning
confidence: 99%
“…A method developed in 2019 of monitoring a user's posture in real time using a smartphone posture application stands out as a cost-effective and accessible solution because smartphones enable self-monitoring and are easy to access. [19][20][21] In addition, the use of digital sound feedback to promptly inform a user of unsafe posture and recognise dangerous postures to improve their self-awareness has been shown to be effective in maintaining a correct working posture in people working on computers 22 and health workers. 23 Therefore, this study aimed to observe changes in working posture by measuring the REBA (Rapid Entire Body Assessment) score of dental hygiene students according to digital sound feedback linked with a smartphone application.…”
Section: Introductionmentioning
confidence: 99%